Exploring Circular Solutions for Economic Growth and Decent Work: SDG 8 and Accounting Perspective - Alamsyahbana, Muhammad Isa; Siregar, Juliani Sari; Antania, Livia (Asosiasi Dosen Akuntansi Indonesia, 2024)
This study aims to explore circular solutions for economic growth and decent work, drawing insights from SDG 8. Embracing a circular economy can promote sustainable development by decoupling economic growth from resource depletion and environmental degradation. Circular practices benefit SDG 8 by creating new job opportunities, fostering innovation, and achieving inclusive economic growth. From an accounting perspective, the study investigates how these circular economy practices impact financial reporting and cost management. By examining the costs associated with recycling, reuse, and recovery of materials and their effects on production expenses and revenues, this research connects circular economy initiatives to sustainable accounting practices. Collaboration among stakeholders - government, private sector, civil society, and the public - is vital for successful implementation. Through collective efforts, Indonesia can move towards a more sustainable and inclusive economy, prioritizing decent work opportunities and environmental responsibility. This study recommends how accounting frameworks can be adapted to reflect the economic and environmental benefits of circular practices, ensuring that financial reporting supports sustainable development goals.